2016
DOI: 10.1021/acs.langmuir.6b01530
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Colloids: Disassembly and Deaggregation

Abstract: We demonstrate a high-resolution method as an efficient tool to in situ characterize partially reversible assembly and aggregation of metal-organic framework (MOF) colloids. Based on the gas-phase electrophoresis, the primary size and the degree of aggregation of the MOF-525 crystals are tunable by pH adjustment and mobility selection. These findings allow for the further size control of MOF colloids and prove the capability of semiquantitative analysis for the MOF-based platforms in a variety of aqueous formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 50 publications
(68 reference statements)
0
37
0
Order By: Relevance
“…4). Previous reports have shown that pH adjustment can manipulate the assembly and aggregation of MOF-525 particles 44,45 and that strongly acidic modulators improve the colloidal stability of UiO-66. 38 More generally, the seesaw model serves as a complement to well-established models of bulk crystal growth and polymer formation.…”
Section: Discussionmentioning
confidence: 99%
“…4). Previous reports have shown that pH adjustment can manipulate the assembly and aggregation of MOF-525 particles 44,45 and that strongly acidic modulators improve the colloidal stability of UiO-66. 38 More generally, the seesaw model serves as a complement to well-established models of bulk crystal growth and polymer formation.…”
Section: Discussionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) have sprung up as a new type of crystalline material, assembled by appending metal ions or metal clusters with organic connecting linkers. [14][15][16][17] It is possible to regulate the characteristics of MOFs by integrating diverse metal cations with varied organic components. [18][19][20] The temperament of MOFs results in different advantages as correlated to customary inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these results suggest that ligand excess, of either linker or modulator, exerts the greatest impact on nanoMOF sizes in general. 43 and that strongly acidic modulators improve the colloidal stability of UiO-66. 38 More generally, the seesaw model serves as a complement to well-established models of bulk crystal growth and polymer formation.…”
Section: Discussionmentioning
confidence: 97%